Minority Youth and Social Transformation in Australia: Identities, Belonging and Cultural Capital - Jakubowicz, Andrew (2014)
Increasingly minority youth, especially from Muslim backgrounds, have been seen in Australian public policy and the media as potentially disruptive and transgressive. In some European societies similar young people have been portrayed as living in parallel and disconnected social spaces, self-segregated from interaction with the wider community. Yet Australian ethnic minority youth do not fulfil either of these stereotypes. Rather, despite their often regular experiences of racism or discrimination, they continue to assert a strong identification with and belonging to Australian society, albeit the society that marginalizes and denigrates their cultural capital. In particular it is the neighbourhood and the locality that provides the bridge between their home cultures and the broader world, contributing to a range of positive aspirations and fluid identities.